2015
DOI: 10.1007/s13105-015-0412-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D attenuates pro-inflammatory TNF-α cytokine expression by inhibiting NF-кB/p65 signaling in hypertrophied rat hearts

Abstract: A growing body of evidence suggests that immune activation and inflammatory mediators may play a key role in the development and progression of left ventricle (LV) hypertrophy. The present study was designed to test the hypothesis that the cardioprotective effect of cholecalciferol (Vit-D3) is mediated via the regulation of messenger RNA (mRNA) expression of pro-inflammatory cytokines. Rats were randomly divided into four groups: control group received normal saline (0.9 % NaCl) i.p. for 14 days; Vit-D3 group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 44 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…Previous studies showed that vitamin D intake might reduce inflammatory factors by inhibiting the production of IL-6 [37,38]. Moreover, vitamin D may inhibit the nuclear factor κB (NF-κB) activity by increasing the expression of IκB, which in turn would result in a significant decrease in the production of pro-inflammatory factors, such as IL-8 [39]. Our meta-analysis of RCTs showed that vitamin D supplementation resulted in a significant increase in TAC and GSH, and a significant decrease in MDA levels in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that vitamin D intake might reduce inflammatory factors by inhibiting the production of IL-6 [37,38]. Moreover, vitamin D may inhibit the nuclear factor κB (NF-κB) activity by increasing the expression of IκB, which in turn would result in a significant decrease in the production of pro-inflammatory factors, such as IL-8 [39]. Our meta-analysis of RCTs showed that vitamin D supplementation resulted in a significant increase in TAC and GSH, and a significant decrease in MDA levels in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been shown to reduce the expression of TNF-␣ by decreasing NF-B-p65 mRNA expression and increasing IB-␣ mRNA expression (9). In a recent study of 118 women, those who were deficient in vitamin D had higher serum levels of TNF-␣ (10).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes, a chronic inflammatory disease, is a risk factor for LVH [30]. Reversal of LVH in diabetic rats [31] and attenuation of TNF-α expression by inhibition of nuclear factor-kappa beta (NF-κB/p65) signaling in hypertrophied rat hearts with vitamin D [32] suggest the role of vitamin D in reversal of LVH. These studies suggest a pathogenic role of vitamin D deficiency in LVH and vitamin D supplementation is cardioprotective.…”
Section: Cardiac Diseasesmentioning
confidence: 99%